A contribution to the knowledge of ascomycetes in eastern Serbia - Iskra Kajevska; Marjan Kuštera; Ivana Cvijetan (Biologica Nyssana, 2018)
Mycological field research conducted from 2015 - 2018 in the eastern part of Serbia resulted with a registration of a new data on 9 insufficiently known or new ascomycetes for the country: Cordyceps militaris, Ophiocordyceps gracilis, Peziza phyllogena, Neottiella vivida, Scutellinia legalie, S. trechispora, Plectania melastoma, Pseudoplectania nigrella and Urnula mediterranea. All species are presented with color photos of fresh specimens, microscopic morphology and notes on their taxonomy, ecology and distribution in the country.